Assistência à saúde de gestantes usuárias de crack: revisão de escopo - Aragão, Heliandra Linhares (2023)
Cocaine/crack consumption during pregnancy has significantly contributed to the risk of maternal health complications. However, these risks go beyond obstetric problems, as they also contribute to damage that considerably affects the neonatal, child and adult health of these fetuses. The assistance provided to pregnant women who use alcohol and/or other drugs is considered highly complex, requiring specific training from the health professionals who will be providing this care. This research will aim to identify the scientific production on care for pregnant women who use crack in the face of the presented problems and the challenges of comprehensive care for this population. For this, we methodologically opted for a literature review, with emphasis on a specific approach called Scope Review. The purpose of this dissertation is organized in presenting the contextualization that has been produced on health care for pregnant women who use crack. To construct the research question, the Population, Concept and Context (PCC) strategy was used. The following were defined: P- Pregnant women who use crack; C- risk pregnant women and C- Health care. Based on these definitions, the guiding question was established: “What is the scientific production on health care for pregnant women who use crack?”. The selection of articles was carried out in three stages, initially a reading of titles and abstracts was done in order to include the works that responded to the research objective, then the studies were read in full and reassessed if they were in the inclusion standard already in the last stage, after the complete reading of the included studies, the summarization of information that replicate the objective of the guiding element. Based on the established criteria, a total of 46 studies were selected, from 2015 to 2021, most of which were published in 2018, 10 in total; regarding the place of publication, 54% were published in Brazil, followed by 26% in the United States and the rest in Spain and Uruguay; 26 of the findings were in Portuguese, 14 in English and the rest in Spanish; In 67% of the studies, the participating public were pregnant users, the rest of the surveys were with professionals and reviews. Faced with the problem of SPA use during pregnancy, with this scope review, it was noticed that the number of scientific studies on assistance to pregnant women who use crack is still relatively low, that is, it has been little studied and, consequently, there are little research evidence on specific recommendations for this population. The complexity of the phenomenon can be portrayed by the difficulty of effectively implementing care, which may result in the scarcity of scientific production on this topic, compared to other relevant health topics.